PENGARUH MOTIVASI BELAJAR TERHADAP MINAT BERWIRAUSAHA SISWA SMA XYZ DI JAKARTA BARAT - Widjaja, William (Jurnal Ilmu Manajemen, 2019)
This study aims to examine the effect of learning motivation on the interest in entrepreneurship of XYZ high school students, in West Jakarta. The method used in this study is a quantitative method using a simple regression test and t test to test the hypothesis. The data used in this study is a primary data using questionnaires as data collection instruments. The number of samples used is 52 respondents with saturated sample techniques. The results of a simple regression analysis show a constant value of 31.438 with a regression coefficient of learning motivation variables of 0.979. The result of the t-test is 5.385 with a significance value of 0.000 (<0.05) which means that there is a significance influences between learning motivation towards the interest in entrepreneurship of high school students XYZ, West Jakarta.